Media Gambar Pembelajaran Bahasa Indonesia Kelas I SDN No. 28 Inpres Luaor (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2023)
Learning is carried out still using conventional media and an emphasis on the teacher. Compared to that, the use of media can help students to more easily understand lessons. This study aims to determine the application of media images in Indonesian language learning class I. This research is a Classroom Action Research (CAR). The learning improvement process was carried out in two cycles. Each cycle consists of two meetings covering the planning, implementation, observation, and reflection stages. This research was conducted at SDN No. 28 Luaor Presidential Instruction, Pamoang District, Majene Regency. In cycle I the researcher planned and then carried out the lesson by explaining the names of the body parts as well as observing the learning process and reflecting at the end of the lesson. In cycle II the researcher did the planning and then carried out the learning by explaining the names of the body parts using image media that contained pictures of the body parts and their names. The implementation of learning is accompanied by observation and reflection. The application of media images in learning Indonesian can assist teachers in providing understanding to students.